ANALYSIS OF PATIENT SATISFACTION TOWARDS SERVICE QUALITYOUTPATIENT REGISTRATION IN THE ERA OF ELECTRONIC MEDICAL RECORDS - Syndia Puspitasari (Suluh Adiluhung Publisher (SAPub), 2026)
To improve the quality of hospital quality, it can be seen from patient satisfaction. The quality of quality service can be seen from how patient services are managed, reviewed from the outpatient registration area. Based on the results of initial observations at Hospital